Model of cylindrical micelles with different endcaps. Issue 5 (4th May 2017) - Jia, X.; Yu, S.; Ma, Y.; Li, X.; Xu, W.; Liu, J.
ABSTRACT: The system of alcohol (C8 OH) and hexadecyl trimethyl ammonium bromide (CTAB) was studied by molecular dynamics simulation, and the cylindrical (or rod-like) micelles with different endcaps were obtained. The simulation results presented the different terminal structures of the cylindrical (rod-like) micelles. According to the critical packing parameters of the micellar stability theory, the microscopic structures of cylindrical (or rod-like) micelles with different endcaps were analyzed. The shorter rod-like micelle was constituted by the cylindrical body and two swelling spherical endcaps, while the longer cylindrical (or rod-like) micelle had two spherical crown endcaps less than the hemisphere. The models of the cylindrical (rod-like) micelles were presented in detail based on the simulation results and the micellar stability theory. GRAPHICAL ABSTRACT: